The Impact of Higher Education on Employer Perceptions - Renske Stans; Laura Ehrmantraut; Malin Siemers; Pia Pinger (Institute of Labor Economics (IZA), 2025)
Do employers seek to attract individuals with more education because it enhances human capital or because it signals higher levels of pre-existing traits? We experimentally vary master's degree completion rates on applicant résumés and examine how this influences candidates' desirability and employer perceptions of their productive characteristics. Our findings show that while a completed master's degree increases desirability, an incomplete master's degree is perceived by human resource managers as less favorable than a bachelor's degree. This suggests that employers prefer candidates with higher education mainly because they view the degree as a signal of pre-existing productive traits. Consistent with this, employers perceive both cognitive and non-cognitive traits as stronger in master graduates but non-cognitive traits as weaker in master dropouts compared to bachelor's degree holders. Overall, perceived cognitive and non-cognitive traits play a larger role in determining a candidate's attractiveness than expertise. This paper thus provides causal evidence on the origins of the education premium.
Keywords: 23; I26; J23; J24; J31; 330; returns to education; beliefs; labor demand; labor productivity; signaling; wages